Assessment of Bird Diversity and Abundance in Three Land Use Change in Bukit Mor Ex-Mining Site, Muar, Johor - Lee, Chun Wai; Norazlimi, Nor Atiqah; Mohd Lokman, Ilham-Norhakim (Enhanced Knowledge in Sciences and Technology, 2025)
Malaysia has a number of ex-mining sites. Ex-mining areas, often seen as symbols of environmental degradation, hold a remarkable potential for transformation into thriving ecosystems. These landscapes can become vital habitats for both migratory and resident bird species through natural vegetation regrowth. Several research has been conducted to survey the avian diversity in the ex-mining sites of Malaysia. However, little is known about these locations' potential as substitute habitats for birds, especially in the Muar district of Johor. A study was conducted in the ex-mining site of Bukit Mor, Muar, Johor from July to October 2024 to assess the bird diversity and its abundance in the area where the objectives were to provide a checklist of avian diversity in Bukit Mor ex-mining site, Muar, Johor, and to compare the diversity of avian in selected land-use changes in Bukit Mor ex-mining site, Muar, Johor. The point count method with the help of a camera, binocular, and sound recording application was utilized to survey the bird diversity and abundance in the sampling area which consists of 3 land-use changes namely, Secondary Forest (Area A), Fruit Plantation (Area B), and Oil Palm Plantation (Area C). A total of 61 species of birds were observed from 37 families, where 31 were observed in Area A, 36 in Area B, and 30 in Area C. The results of the diversity indices in each microhabitat were high which shows that each microhabitat has high bird diversity. The Kruskal-Wallis test shows that there are no statistically significant differences in median bird species counts across the three land-use changes, which might imply that the land-use changes were very close to one another, thus the birds can fly and move to each microhabitat with no difficulty. Besides, the Species Accumulation Curve shows that the line in the graph has not reached an asymptote yet, indicating that there should be more species to be discovered in the area. Conclusively, the study showed that reclaimed ex-mining sites are suitable for birds to live, and the area has the potential to be a spot for avitourism.